Diagnostic challenges in hemangioblastoma: lessons from a rare case presentation - Jayeshkumar Kanani (Egyptian Journal of Neurosurgery)
Abstract Background Hemangioblastomas are rare, slow-growing benign neoplasms predominantly affecting the central nervous system (CNS). Despite their benign nature, they pose diagnostic challenges due to their diverse clinical manifestations and radiological features. Case presentation. A 40-year-old male presented with chronic headaches and diplopia persisting for 8 years. Initial MRI revealed two cystic lesions in the cerebellum, causing compression and herniation. Surgical removal of one cyst yielded inconclusive results. Follow-up MRIs showed cyst growth and syrinx development. The patient collapsed suddenly at home and was pronounced dead on arrival at the hospital. Postmortem examination revealed multiple small nodules on the surface of the meninges, with corresponding punched-out lesions on the inner surfaces of the cranial bones. These nodules were attached to the brain surface upon meningeal removal. Additionally, multiple cysts, 3–5 cm in length and 2–3 cm wide, were observed over the right cerebellar lobe, containing transparent yellowish fluid. Pathological examination revealed features of gliosis, pneumonia, and chronic pyelonephritis. Despite suggestive radiological features, confirming cerebellar hemangioblastoma proved challenging. Conclusions The patient’s sudden demise underscores the importance of accurate diagnosis and multidisciplinary management to optimize outcomes. Early recognition and intervention are crucial to mitigate complications associated with untreated hemangioblastomas.